Functional Dyes, and Some Hi-Tech Applications - Reda M. El-Shishtawy (International Journal of Photoenergy)
An overview of the recent developments in functional dyes, which are useful for hi-tech applications for those based on optoelectronics, such as dye sensitized solar cells, photochromic dyes and biomedical applications, such as photodynamic therapy for the treatment of cancer and fluorescent sensors is presented.